2002
DOI: 10.1159/000065432
|View full text |Cite
|
Sign up to set email alerts
|

The ORL<sub>1</sub> Receptor: Molecular Pharmacology and Signalling Mechanisms

Abstract: The cloning of the opioid-receptor-like 1 (ORL1) receptor and the identification of nociceptin as its endogenous agonist have revealed a new G-protein-coupled receptor signalling system. The structural and functional homology of ORL1 to the opioid receptor systems has posed a number of challenges in understanding the often competing physiological responses elicited by these G-protein-coupled receptors. Thus, this review will attempt to summarize recent research by many groups that has rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 135 publications
(182 reference statements)
2
52
0
Order By: Relevance
“…Previous in vitro studies reported stimulatory actions of N/OFQ on ERK signaling pathways in cell lines transfected with NOP receptor (Fukuda et al, 1997;New and Wong, 2002). Here, we show that in living animals NOP receptor activation inhibits ERK pathway in the hippocampus.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Previous in vitro studies reported stimulatory actions of N/OFQ on ERK signaling pathways in cell lines transfected with NOP receptor (Fukuda et al, 1997;New and Wong, 2002). Here, we show that in living animals NOP receptor activation inhibits ERK pathway in the hippocampus.…”
Section: Discussionsupporting
confidence: 64%
“…NOP receptor is a G-protein-coupled receptor that negatively regulates the activity of adenylate cyclases, inhibits voltage-gated Ca 2ϩ channels and activates inward rectifying K ϩ channels. By blocking Ca 2ϩ current and inhibiting cAMP production (New and Wong, 2002), NOP receptor can suppress the activation of multiple cascades that ultimately converge on ERK, and thereby disrupts NMDA receptor-mediated recognition memory formation. In this regard, Mamiya et al (2003) have shown that NOP and NMDA receptors modulate in an opposing manner the activity of Ca 2ϩ /calmodulin-dependent protein kinase II (CaMKII) in hippocampal slice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because ORL1 receptors and opioid receptors, in general, are well established to couple to PTX-sensitive G␣ i/o protein subunits (New and Wong, 2002), we found that Ca 2ϩ channel inhibition was significantly decreased in SG neurons pretreated with the toxin. Similar findings have been previously published (Morikawa et al, 1998;Connor et al, 1999;Larsson et al, 2000;Beedle et al, 2004;Yeon et al, 2004).…”
Section: Discussionmentioning
confidence: 86%
“…ORL1 receptors are coupled to members of the pertussis toxin (PTX)-sensitive G␣ i/o G protein family. Stimulation of ORL1 receptors by Noc results in inhibition of voltage-gated Ca 2ϩ channels, activation of G protein-gated inwardly rectifying K ϩ channels, and negative coupling to adenylyl cyclases (for review, see New and Wong, 2002).…”
mentioning
confidence: 99%